Geometrični popravki optičnih satelitskih posnetkov - Kosmatin Fras, Mojca (Prostor, kraj, čas, 2018)
The monograph presents a fully automated procedure for geometric correction of optical satellite images, without any manual intervention during the processing. The resulting orthorectified image is in the national coordinate system and constitutes a suitable source for spatial analyses. In the monograph the original procedure connects several different methods into a single, robust system for automatic generation of orthoimages is documented in detail. The work describes the whole automatic orthorectification process, which comprises four basic modules: a module for extracting and preparing the metadata, a module for automatic extraction of ground control points, a module for calculation of parameters of the geometric model, and a module for orthorectification. The experiments and results with RapidEye and WorldView-2 images are also presented. The experiments evaluate the procedure for automatic extraction of points, the geometric model, the elimination of gross errors, and the positional accuracy of the orthoimages. The analisys of the results indicate that the automated procedure produces orthoimages with a positional accuracy of about two pixels or better, even if several gross errors are present among the automatically extracted ground control points.